PENDIDIKAN KEWARGANEGARAAN BERBASIS KARAKTER SEBAGAI SARANA PEMBENTUKAN MORAL SISWA KELAS IX SMP NEGERI 1 SENDANG TULUNGAGUNG - Deca Yusuf Seven Juliano; Mohammad Hasib; Bachrul Ulum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of students' moral development amidst technological advancement, globalization, and increasingly complex challenges in adolescent behavior. Character-based Civic Education (PPKn) has a strategic role in instilling moral values, character, and nationalistic attitudes in students. The purpose of this study is to describe the implementation of character-based Civic Education as a means of moral development for ninth-grade students at SMP Negeri 1 Sendang Tulungagung and to identify the factors influencing its implementation. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of Civic Education teachers, Guidance and Counseling (BK) teachers, and ninth-grade students of SMP Negeri 1 Sendang Tulungagung. Data were collected through interviews, observations, and documentation. Data analysis was conducted using the Miles, Huberman, and Saldaña model, which includes data condensation, data display, and conclusion drawing. Data validity was ensured through source triangulation and method triangulation. The findings indicate that character-based Civic Education at SMP Negeri 1 Sendang Tulungagung is implemented through the integration of character values into lesson planning, classroom learning activities, teacher role modeling, the enforcement of school regulations, and the habituation of positive behavior in daily life. The character values developed include religiosity, honesty, discipline, responsibility, tolerance, and nationalism. Factors influencing students' moral development include family background, school environment, peer groups, technological and social media developments, and students' individual awareness. Therefore, character-based Civic Education has proven to be an effective means of supporting the moral development of ninth-grade students at SMP Negeri 1 Sendang Tulungagung.